The Efforts of Stunting Prevention Through Increasing Maternal Knowledge: a Cross Sectional Study in Pemalang, Central Java - Wijayanti; Sri Handayani; Anik Enikmawati; Ratnasari, Nita Yunianti (STIKes Patria Husada Blitar, 2024)
Stunting refers to a condition characterized by short or very short stature based on the length/height for age, below -2 Standard Deviation (SD) on the WHO growth curve. This condition typically appears from chronic malnutrition, which is often linked to low socioeconomic status, inadequate nutritional intake, maternal health issues, a pattern of recurrent illness, and inappropriate feeding practices during infancy and early childhood. Stunting becomes a serious health problem and requires immediate treatment. In this case, the Indonesian government has made several efforts to improve the reduction of stunting as stated in the 2018 national plan. The World Health Organization (WHO) estimates that 22,2% or 149,2 million children under 5 years old will be stunted by 2020. This research is quantitative type with a cross sectional approach. The independent variable in this study involved mothers' knowledge about stunting as well as being the population, while the dependent variable was the prevention efforts in toddlers. The sampling technique employed probability sampling, namely by stratified random sampling. Inclusion criteria in this study were: a) Mothers and children under five, who live in the RW 01 area of Banyumudal Village, Moga District, Pemalang Regency; b) Mothers who have children under five years old; c) Understand Indonesian; d) Physically and mentally healthy, and e) Willing to be a respondent. The results of the Chi Square test with an error degree of α = 0,05 obtained a p value = 0,001 < α = 0,05. It means that there is a correlation between maternal knowledge about stunting and efforts to prevent it in toddlers in RW 01 Banyumudal Village, Moga District, Pemalang Regency. Stunting will affect long-term brain development, which in turn affects cognitive ability and school performance